The Effects of Resistance Exercises and Yoga on the Life Quality and the Muscle Strength of Patients with Knee Osteoarthritis: A Systemic Review of the Previous Literatures - Vahid Mazloum; Vahid Sobhani (Fasa University of Medical Sciences, 2016)
Background & Objective: Knee osteoarthritis (OA) is a common musculoskeletal disorder in elderly population leading to pain, disability, muscle weakness, and decreasing quality of life (QOL). The objective of the present study was to investigate the effects of land-based exercise therapy intervention on QOL and muscle strength in patients with knee OA in previous researches. Materials & Methods: English literature associated with the effects of land-based therapeutic exercise methods were extracted from Medline, PubMed, CINAHL, Medlib, IrMedex, Magiran, Spring link, Scopus, Cochrane, and Science Direct databases since 2000 to 2016. After applying inclusion and exclusion criteria, 11 articles remained to be reviewed. Results: There were 1200 patients (Mean ± Standard deviation 64.5±4.7 years of old) with knee OA in those eleven studies. Generally, two interventions were administrated for such patients including exercise therapy and Yoga. The most common treatment outcome measurements involved Western Ontario and McMaster Universities Arthritis Index (WOMAC), Short Form 36 (SF-36), and strength. Conclusion: Although it was impossible to compare the results of the eleven studies due to inconsistency in outcome measurements and their units to introduce the most effective therapeutic intervention for improvement of QOL in individuals with knee OA, the positive effect of land-based exercise therapy on signs and symptoms of such disorder was confirmed.